Penerapan Metode Additive Ratio Assessment (ARAS) dan Ranking of Centroid (ROC) dalam Pemilihan Layanan Akomodasi dan Local Cuisine - Yerik Afrianto Singgalen (Journal of Computer System and Informatics (JoSYC), 2023)
Salatiga is a gastronomic city with various types of traditional food and drinks and is a recreational tourism city with exciting and crowded mountain natural scenery. The availability of accommodation services and local cuisine adds to visitors' preferences to enjoy local culinary dishes. This study offers an initiative to use the Additive Ratio Assessment (ARAS) method in selecting the best accommodation and restaurant services in Salatiga based on Tripadvisor data. The stages in the calculation process based on the ARAS method are as follows: the stage of determining the value of criteria, weights, alternatives, and optimal values; the stage of converting the value of the criterion into a decision matrix; the stage of normalization of the decision matrix for all criteria; stage of calculating the value of utility; Ranking stage. The calculation results show that in the context of accommodation services, A5 occupies the first position with a Ki value of 0.887, A4 occupies the second position with a Ki value of 0.870, and A1 occupies the third position with a Ki value of 0.849. Meanwhile, in the context of local cuisine, A2 occupies the first position with a Ki value of 0.951, A5 occupies the second position with a Ki value of 0.914, and A4 occupies the third position with a Ki value of 0.854. This shows that ARAS and ROC methods can produce the best recommendations for tourists who want to use accommodation services and enjoy local cuisine in Salatiga City.